Is there a world Lutheranism? Accountability and representation in ecumenical dialogue. Issue 2 (20th May 2019) - Appold, Kenneth G.
Abstract: The following thoughts were occasioned by my experiences representing the Lutheran World Federation (LWF) and the Evangelical Lutheran Church in America (ELCA) in a variety of international ecumenical dialogues over the past thirteen years. I reflect on some of the fundamental challenges faced by many Lutherans as we seek to represent, as conscientiously as possible, the global communion of which we are members. The question we face is a very simple one: Whom do we represent?